INVESTIGATION ON ESTABLISHED OPERATIONAL MODES OF FREQUENCY-CONTROLLED INDUCTION GENERATOR OF WIND POWER PLANTS - R. I. Mustafayev; R. A. Saidov; L. G. Hasanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes an analytical expression for calculating a manipulated variable of stator voltage in a frequency-controlled induction generator with a cage rotor of a wind power plant while regulating a constant value of the absolute slip of the generator. Comparison of the calculated results by the proposed expression and full differential equations of the generator (an equation of state) at steady state has confirmed a high accuracy of the analytical expression.